Propozycja klasyfikacji szoków gospodarczych jako uzupełnienie teorii optymalnych obszarów walutowych - Czaja, Jarosław (The Classification of Economic Shocks Proposition as the Supplement of Theory of Optimal Currency Areas, 2007)
The need of keeping the optimal currency area in good condition in order to stand economics shocks forces the coordination of policy between fiscal and monetary executives. What they do, it must be predictable for the actors of markets, because it is needed to keep the economic balance. The European Monetary Union must manage many different economic shocks. The purpose of this article is to present the proposition of symmetric and asymmetric shocks' classification. It is very important, because it can help one better understand these phenomena.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (15); 2007; nr 1166, s. 121-129